Freedom is the bread of the spirit (What does the wise and freedom-loving man and slave-owner-democrat Thomas Jefferson teach us?) - Grancharov, Angel (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2020)
The author rethinks the activities and views of Thomas Jefferson in the context of modernity, in particular his attitude to the problems of freedom, human rights, the formation of democracy, the art of government, etc.